2012
DOI: 10.3945/jn.111.150219
|View full text |Cite|
|
Sign up to set email alerts
|

Greater Fructose Consumption Is Associated with Cardiometabolic Risk Markers and Visceral Adiposity in Adolescents3

Abstract: Though adolescents consume more fructose than any other age group, the relationship between fructose consumption and markers of cardiometabolic risk has not been established in this population. We determined associations of total fructose intake (free fructose plus one-half the intake of free sucrose) with cardiometabolic risk factors and type of adiposity in 559 adolescents aged 14-18 y. Fasting blood samples were measured for glucose, insulin, lipids, adiponectin, and C-reactive protein. Diet was assessed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 45 publications
4
65
0
1
Order By: Relevance
“…In humans, the increase of fructose consumption is strongly associated with a steady increase in obesity, insulin resistance, and other metabolic syndromes. 44,45 In addition, several studies in humans and mice suggest that fructose and glucose, the most common dietary sugars, are absorbed in distinct regions of the gastrointestinal tract and metabolized differently, 46,47 and that fructose and glucose affect brain activity and feeding behavior in a disparate manner. 48,49 Thus, it will be interesting to see whether this sugar-and a specific receptor for it-plays also a role in nutrient sensing in mammals.…”
Section: Corazonin Is the Likely Neurotransmitter In Gr43amentioning
confidence: 99%
“…In humans, the increase of fructose consumption is strongly associated with a steady increase in obesity, insulin resistance, and other metabolic syndromes. 44,45 In addition, several studies in humans and mice suggest that fructose and glucose, the most common dietary sugars, are absorbed in distinct regions of the gastrointestinal tract and metabolized differently, 46,47 and that fructose and glucose affect brain activity and feeding behavior in a disparate manner. 48,49 Thus, it will be interesting to see whether this sugar-and a specific receptor for it-plays also a role in nutrient sensing in mammals.…”
Section: Corazonin Is the Likely Neurotransmitter In Gr43amentioning
confidence: 99%
“…The consequent lower activation of lipoprotein lipase in subcutaneous adipose tissue increases availability of triglycerides and their uptake into VAT. 3 This dietary fructose-visceral fat relationship has also been reported in a recent article by Pollock et al, 4 who conclude that greater fructose consumption is associated with multiple markers known to increase the risk for cardiovascular disease, such as blood lipids and inflammatory adipocytokines, suggesting that these relationships are dependent on visceral obesity.…”
Section: To the Editormentioning
confidence: 67%
“…Inadequate statistical power (n=16) and short follow-up period (1 week) may have limited the ability to detect group differences in this trial. In a larger, more recent crosssectional study of adolescents without T1D, total fructose consumption was found to be associated with increased plasma triglycerides and LDL-cholesterol and low HDLcholesterol (31). Among healthy Swiss children, dietary fructose was found to be a significant positive predictor of small LDL-particle size (a marker for increase CVD risk) but not plasma triglycerides (32).…”
Section: Discussionmentioning
confidence: 99%